(untitled) (Journal of history, 2019)
In this article, the author examines the activities and policies of Khaknazar Khan, who ruled in the 40-80’s. XVI century, at the time of the revival of the Kazakh Khanate and the personal human qualities of the Khan, the problems of Khaknazar Khan’s relationship between the rulers of Muerennakhr in the 70s of the mentioned century are also considered. At this time, the political situation of Mauerannakhr was complicated, the process of power struggle divided into two political groups – the Baba Sultan group in Tashkent and the Abdallah Khan group in Bukhara. In the interests of the Kazakh people, Khaknazar Khan supported the ruler of Bukhara. He died during the struggle with Baba Sultan.